THERMALLY STABLE MONTMORILLONITE/SAND COMPOSITE FOR THE REMOVAL OF PHENAZOPYRIDINE FROM WATER BY ADSORPTION, FOLLOWED BY THERMAL REGENERATION: REUSABILITY IN BATCH AND CONTINUOUS FLOW SYSTEMS - Madi, Shatha (An-Najah National University, 2025)
Since water is the essence of life, preserving it is imperative. However, the problem of pharmaceutical contamination in water sources has grown to be a global concern due to recent developments, particularly in the industrial and pharmaceutical sectors. The expulsion of waste products draining into water sources, primarily by industrial and human waste, is causing severe damage, ranging from aquatic life to human health. Therefore, finding efficient, eco-friendly, and low-cost methods that can be applied on a large scale for practical water purification is the general direction recently. In order to process water pollution with pharmaceutical contaminants, an effective and sustainable method is presented in this work using adsorption integrated with the thermal decomposition technique. Adsorptive removal of the pharmaceutical model phenazopyridine hydrochloride (PHY) from water was applied using the prepared adsorbent montmorillonite/sand composite (Mnt/sand), which is repeatedly regenerated by thermal decomposition of the adsorbed PHY, considering the high thermal stability of the adsorbent material. In addition to the batch system, this method was applied to the column system as a practical application. Variant parameters are examined for both systems, examining the supervision adsorption process and its mechanism. For the batch system, the effects of pH, initial concentration, adsorbent amount, and temperature were determined and optimized. The adsorption showed high efficiency in the acidic region, with a maximum percentage of removal 91% at pH 5, which is parallel to the initial pH of the PHY solution, also neutral pH gave relative performance, but decreased at high basic medium pH (10). Adsorption was increased as the amount of Mnt/sand increased, with an optimized amount of 0.5 g, removing 96% of 20 ppm, 100 mL PHY solution reaching the equilibrium within 20 minutes (pH 5, 25◦C). For the initial concentration parameter, inverse relations exist, as it increased the efficiency decreased. Langmuir isotherm model with the highest fitting (R2 = 0.99) indicated a monolayer adsorption mechanism with a homogeneous surface for the adsorbent. The Kinetic study determined the order of the adsorption process, which followed pseudo-second order model. In addition, activation energy was calculated, taking a value of 30.4 kJ/mol. Thermodynamic parameter values specified spontaneous and endothermic adsorption, as a result of negative values of ΔG at different temperatures, and the positive value of ΔH, respectively, implying a strong affinity between PHY and Mnt/sand. Column adsorption experiments were considered with various parameters involving flow rate, concentration, effluent temperature, and column height. A decrease in the flow rate of the effluent enhanced the adsorption performance. The same for concentration, as it decreased the adsorption efficiency increased. While improved column working was observed with a longer column height. Optimized column parameters were determined through continuous adsorption experiments to be 10 ml/min, 50 ppm, 6 g, 8 cm,25 ◦C, pH 5, which revealed a high efficiency performance of 97%. Characterization of Mnt/sand described its components and structural features. X-ray diffraction (XRD) indicated a high degree of crystallinity of Mnt/sand, and it showed sand and montmorillonite peaks combined in the spectrum, emphasizing the emergence of both sand and montmorillonite. Scanning electron microscopy (SEM) revealed porosity and aggregation of the adsorbent granules. Thermogravimetric analysis (TGA) was essential to approve the thermal stability of adsorbent material, which was detected for Mnt/sand up to 800 ◦C. Also, it was used to determine the thermal decomposition temperature of free PHY, which was found to be 650 ◦C. Fourier transform infrared (FT-IR) spectrum of the contaminated Mnt/sand evidence PHY adsorption, due to the appearance of PHY peaks in the spectrum, while the disappearance of PHY functional groups peaks after regeneration asserts that thermolysis left a clear adsorbent afterwards. The reusing process was based on the thermolysis technique, which was applied to the polluted adsorbent, breaking adsorbed PHY molecules into CO2, H2O, and other volatile gases at 650 ◦C, whereas the Mnt/sand maintains its efficiency during thermal regeneration operation, according to its high thermal stability. Thermolysis temperature study supported with computational study was applied to investigate the possibility of saving energy by reducing the temperature required for thermolysis, minimizing it to 550◦C showing equivalent performance, without any efficiency loss. In conclusion, these results showed operative performance for both batch and column systems, using the prepared adsorbent Mnt/sand for adsorptive removal of PHY. This validates using the adsorption-thermolysis technique as an efficient, economical, scalable, and reusable technique for water treatment from pharmaceutical pollutants.
تحضير واستخدام مركب من المونتموريلونيت/الرمل المستقر حراريًا لإزالة الفينازوبيريدين من الماء بالامتزاز، متبوعًا بالتجديد الحراري: قابلية إعادة الاستخدام في أنظمة الدُفعات والتدفق المستمر